A BILINGUAL CHILD’S ACQUISITION OF MANDARIN AND ENGLISH: SAME OR DIFFERENT RATE? - Kuang Ching Hei (Indonesian JELT, 2011)
This paper is descriptive in nature. It looks at the utterances of one Malaysian-Chinese bilingual child who was specifically spoken to in Mandarin and English from birth. The aim of this paper is to highlight the different speech components present in the two languages. There is some evidence to show that the child's preferred language is not necessarily the dominant language. The child was observed closely by the researcher cum mother over a period of seven months. Initial utterances were tape recorded but later discarded due to impracticality. Subsequent utterances were then spontaneously recorded into journals as and when they occurred within the child’s home with details such as time, date, place and participants indicated. Transcribed orthographically, data were then categorized according to the languages heard and then the speech components (see Hoff, 2009; Foster-Cohen, 1999; Crystal, 1997) respectively. A frequency count of all these utterances suggests that 59% of the child’s utterances were in English while 19% were in Mandarin (dominant language) with smaller percentages subscribing to the various environmental languages. Data also indicate that more nouns were used in English and but slightly more verbs and noun phrases were used in Mandarin. This phenomenon was also used as a determinant to gauge the rate of acquisition of the two languages. A very small percentage of the child’s data were also articulated as complete sentences but this was done in mixed languages, which could be a typical phenomenon of bilingual language acquisition at the early stage.      Keywords: bilingual language acquisition, Malaysia, Mandarin, English, grammar